Sex Cord-Stromal Tumors of Testis: A Clinicopathologic and Follow-Up Study of 15 Cases in a High-Volume Institute of China - Huang, Yin; Chen, Bo; Cao, Dehong; Chen, Zeyu; Li, Jin; Guo, Jianbing; Dong, Qiang; Wei, Qiang; Liu, Liangren (Frontiers in Medicine, 2022)
Objectives To report the first series of testicular sex cord-stromal tumors (TSCSTs) with detailed clinicopathologic findings and long-term follow-up in the Chinese population. Patients and Methods From 2008 to 2018, 15 patients with TSCST were included in our study. The tumors were analyzed for epidemiological parameters, clinical characteristics, tumor markers, therapy, and follow-up data. Results The median age of the patients was 28 years (range, 13–80 years). Para-aortic lymph node metastases were detected in 2 patients after radiological evaluation. Orchiectomy was performed in all patients, and the median diameter of the tumor was 1.5 cm (range, 0.5–5.0 cm). Nine Leydig cell tumors (LCTs), 5 Sertoli cell tumors (SCTs), and 1 unclassified type were confirmed after pathologic evaluation. Thirteen patients (86.7%) were categorized as stage I, and 2 patients (13.3%) were categorized as stage II. The median clinical follow-up was 39.0 months (range, 5–97 months), which showed 10 alive patients, such as 1 patient with progression at 40 months after orchiectomy. The 3- and 5-year progression-free survivals were 100 and 90.0%, respectively. Conclusion Testicular sex cord-stromal tumor at stages I and II is a rare subtype with benign behavior and a favorable prognosis in the Chinese population. However, lymph node metastases may be the dominant risk factor for patients with TSCST.